THE CONNECTING FUNCTION OF TRANSLATION AND WAYS TO ACHIEVE MUTUAL UNDERSTANDING IN TRANSLATION - Eliboyeva Kamola Ramazonovna; Guli Ergasheva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Translation is a vital tool for communication between people who speak different languages. It serves as a bridge that connects people from different cultures and backgrounds, allowing them to share ideas, knowledge, and experiences. However, translation is not just about converting words from one language to another. It also has a connecting function that helps to achieve mutual understanding between people. The connecting function of translation refers to the ability of translation to bring people together by facilitating communication and understanding. Translation helps to break down language barriers and enables people to communicate with each other in a way that is meaningful and effective. It allows people to share their thoughts, ideas, and experiences, and to learn from each other.